Korban Kekerasan Rumah Tangga: Adat Dayak Uud Danum dan Hukum Nasional - Kartika Agus Salim (Fakultas Hukum Universitas Bangka Belitung, 2023)
Law Number 23 of 2004 concerning the Elimination of Domestic Violence and the 2001 Uud Danum Dayak Customary Law Book have provided protection for wives who are victims of domestic violence by their husbands. The protection provided by Law Number 23 of 2004 concerning the Elimination of Domestic Violence is provided from the time the victim makes a police report, when he is questioned and arrives at a court decision. Legal protection provided by Tomakung to wives who are victims of violence (hotuhui) by husbands by paying fines and implementing siro sahkik to restore conditions damaged by violence (hotuhui) between husband and wife. Factors that cause domestic violence by husbands are caused by internal and external factors. Internal factors are caused by wives who cheat, wasteful with money, lazy to cook. Internal factors in husbands are due to being lazy to work, not having a job, having an affair, gambling and being an alcoholic drink addict. The government should provide jobs for all levels of education that are evenly distributed from villages to cities. The government should, in helping the poor, not provide social assistance in the form of direct cash assistance because a small nominal amount of money is only enough to buy alcohol and play gambling. The increase in domestic violence is not solely the fault of the citizens but due to a lack of community awareness raising by the central and regional governments that is right on target because today the Government is building more infrastructure than building the mental and spiritual Indonesian people themselves.